Analysis of the Role of Information and Communication Tech-nology (ICT) in Enhancing the Managerial Capacity of SMEs for Achieving Local Economic Sustainability - Yani, Ahmad (Technology and Society Perspectives (TACIT), 2024)
Small and Medium Enterprises (SMEs) play a significant role in driving the local economy in many countries. SMEs contribute significantly to job creation, increasing per capita income, and reducing economic disparities. This research aims to examine the role of ICT in enhancing the managerial capacity of SMEs for achieving local economic sustainability. The research methodology employed in this study is a qualitative literature review that draws data from Google Scholar for the period 2012-2024. The study findings indicate that ICT has great potential in transforming the business paradigm of SMEs. Through appropriate adoption and adequate support, ICT enables SMEs to enhance operational efficiency, expand market reach, improve access to information and resources, and foster innovation and collaboration within the local business ecosystem.